2016
DOI: 10.4067/s0718-58392016000200002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and path coefficient analysis of Southern African maize hybrids

Abstract: Detailed knowledge on genetic diversity among germplasm is important for hybrid maize (Zea mays L.) breeding. The objective of the study was to determine genetic diversity in widely grown hybrids in Southern Africa, and compare effectiveness of phenotypic analysis models for determining genetic distances between hybrids. Fifty hybrids were evaluated at one site with two replicates. The experiment was a randomized complete block design. Phenotypic and genotypic data were analyzed using SAS and Power Marker resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
5
5
0
1
Order By: Relevance
“…These results are similar to those reported by Ghimire & Timsina (2015). EW showed a positive correlation of r = 0.993 and r = 0.991 with GY for early maturing and super-early maturing genotypes, respectively, corroborating the results of Mhoswa et al (2016) and Ghimire & Timsina (2015).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These results are similar to those reported by Ghimire & Timsina (2015). EW showed a positive correlation of r = 0.993 and r = 0.991 with GY for early maturing and super-early maturing genotypes, respectively, corroborating the results of Mhoswa et al (2016) and Ghimire & Timsina (2015).…”
Section: Resultssupporting
confidence: 82%
“…In early maturing genotypes, the estimates of phenotypic correlation ranged from r = -0.847 between FF and EI and between FF and NE to r = 0.993 between EW and GY (Table 3). A positive correlation among EW and GY (r = 0.64) was also found by Mhoswa et al (2016). In super-early maturing genotypes, the estimates of Pesq.…”
Section: Resultsmentioning
confidence: 70%
“…The negative direct effect of plant height on the grain yield of this finding at Bambasi is similar with the pervious finding Sreckov et al (2011) while partially contradicted with the finding of Kumar et al (2006) and Patil et al (2016) who reported that plant height and EBM showed positive direct effect on the grain yield. The positive direct effect of root biomass on the grain yield agreed with the findings of Mhoswa et al (2016) and Silva et al (2016) who reported that root dry matter and root fresh weight had positive direct effect on grain yield which directly related with the nitrogen absorption capacity of the crop that helps to afford the nutrient demand of the crop and increasing the yield. Therefore direct selection of these traits is advisable for improving the grain yield.…”
Section: Genotypic Path Coefficient Analysissupporting
confidence: 88%
“…Understanding the direct and indirect effects on a main trait according to the variation of the others (explanatory) can help in the weighting of the traits for the selection indices and in the estimation of the correlated response in breeding programs (Mhoswa et al., 2016; Rios, Borém, Guimarães, & Paes, 2012). In path analysis, to declare that the effect of a primary trait is significant, and that the trait is a candidate for combined selection, the estimate of the direct effect on the main trait must be greater than the residual effect.…”
Section: Resultsmentioning
confidence: 99%